Estimation of iron losses in a SynRM with segmented rotor - Mohd Azri Hizami, Rasid (Institute of Electrical and Electronics Engineers Inc., 2022)
Besides the copper losses and mechanical losses, iron losses are inevitably reducing the efficiency of an ac machine. Despite being generally agreed to be much smaller in proportion in comparison to copper losses at lower speed, it is nonetheless necessary to be estimated before concluding that it could eventually be neglected for further studies like thermal analysis. In this study, the iron losses in a 180W SynRM machine with segmented rotor was estimated using Bertotti iron losses model across its operating area. The peak flux density across the laminated core was determined using FE analysis where the harmonics are neglected in this preliminary study. The hysteresis and excess losses' coefficient was determined by curve-fitting the Epstein data of the material which is a M330-50A lamination. The results show a maximum iron losses of only 4.9W across the operating area of the machine, occurring at the operating point of (torque; speed) = (0.21N.m; 6800rpm). The Eddy current losses makes the biggest part of it at 2.8W.